Improving rural water supply in Mexico in times of pandemics - Silva, Jorge (Tecnología y ciencias del agua, 2023)
The efficacy of public administration strategies has been gauged on how they handle pandemics and the knock-on effects that occur on the environment or society, and in this case, in the rural water supply in Mexico in times of pandemics. Water access in rural Mexico and how the government has managed the rise in demand during pandemics are explored using a systematic review into 51 documents. Mexico’s water system is below par and there is a need for more investments to be pumped into community management schemes. The involvement of the public in the development of community management schemes is necessary to find a solution to the changing demand and supply.